A Study On The Compatibility Of Passport To The World 3, Fun And Easy English Book For Grade IX For Junior High School Student, With School Level - Based Curriculum - ANINDYAWATI, FIBRIAN (2012)
This study is mainly intended to find out whether the English textbook used for the third year student of junior high school "Passport to the World 3, Fun and Easy English Book for Grade IX for Junior High School Student" is compatible with indicators of the language skills suggested by School Level - Based Curriculum. In line with the objectives of the research, the writer used a descriptive research. In collecting the data, she used document as data source. The data were analyzed by these steps: (1) presenting the materials, (2) comparing the materials, (3) giving the percentage, (4) judging whether the English textbook is appropriate with School Level - based Curriculum, (5) drawing conclusion. The result of the analysis shows that the percentage of the appropriateness of the skills developed in the textbook is 55, 38%. It means that in developing the language skill the textbook is fairly good or compatible with the School Level - based Curriculum. The language skills which are developed in the textbook are involved: the compatibility of listening materials is 59, 09% or fairly good with the indicators of School Level - based Curriculum, the compatibility of speaking materials is 68, 75% or good with the indicators of School Level - based Curriculum, the compatibility of reading materials is 44, 44% or fairly good with the indicators of School Level - based Curriculum, the compatibility of writing materials is 59, 09% or fairly good with the indicators of School Level - based Curriculum. This research implies that the textbook entitled "Passport to the World 3, Fun and Easy English Book for Grade IX for Junior High School Student" is fairly good materials to support the teaching-learning process. The materials of listening, reading, and writing are not adequate. This English textbook needs the other materials to support the teaching-learning activities.